PENGARUH EKSISTENSI TRANSPORTASI UMUM BUS RAPID TRANSIT MAMMINASATA TERHADAP DAYA TARIK ANGKOT DI KOTA MAKASSAR - Rusdi, Rusdi; Wulandari, Andi Triwenni; Ibrahim, Ibrahim (UNM Geographic Journal, 2023)
This research was conducted to find out: 1) Description of the existence of the mamminasata bus rapid transit public transportation, 2) Description of the attractiveness of public transportation in the city of Makassar, 3) how does the existence of the mamminasata rapid transit bus affect the attractiveness of public transportation in the city of Makassar. The research method used in this study is a descriptive quantitative approach method. The research variables consist of the existence of the mamminasata rapit transit bus(Variable X) and the attractiveness of public transportation (Variable Y). The techniques  used for data collection are observation, questionnaires or questionnaires as well as documentation. The data analysis technique used is descriptive statistics and inferential analysis. Based on the research results, it is known that: 1) The description of the existence of the Mamminasata rapid transit bus (variable X) in the "doubtful" category determines the results of data acquisition from filling out the questionnaire which is presented based on indicators of security, safety, comfort, affordability, repair, service. There were 81 respondents who answered doubtfully from a sample of 100 respondents. This shows that overall the existence of bus rapid transit is still in doubt. 2) The description of the attractiveness of public transportation in Makassar City (variable Y) is in the "doubtful" category. In the data obtained from filling out the research questionnaire based on the comfort of the indicators, the feeling of being comfortable clean, accessibility, facilities and infrastructure. There were 62 respondents who answered in doubt, this shows that those who dominated the filling out of the research questionnaire were in doubt. Therefore, the attractiveness of public transportation in the city of Makassar is included in the "low" category, why is that? "Low" transportation in the city of Makassar is included in the"low" category, why is that? Which shows the level of influence that is "low"